2017
DOI: 10.18632/oncotarget.20372
|View full text |Cite
|
Sign up to set email alerts
|

Interest of integrins targeting in glioblastoma according to tumor heterogeneity and cancer stem cell paradigm: an update

Abstract: Glioblastomas are malignant brain tumors with dismal prognosis despite standard treatment with surgery and radio/chemotherapy. These tumors are defined by an important cellular heterogeneity and notably contain a particular subpopulation of Glioblastoma-initiating cells, which recapitulate the heterogeneity of the original Glioblastoma. In order to classify these heterogeneous tumors, genomic profiling has also been undertaken to classify these heterogeneous tumors into several subtypes. Current research focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
96
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 157 publications
(245 reference statements)
2
96
0
Order By: Relevance
“…Another noteworthy GO term was integrin binding (FDR = 0.037). Integrins are transmembrane proteins that mediate cell adhesion, play an important role in promoting the invasiveness of glioma cells [48], and have been suggested as potential targets with diagnostic and prognostic value in glioma [49]. Several enriched GO terms were related to the activity of endopeptidases and collagen.…”
Section: Resultsmentioning
confidence: 99%
“…Another noteworthy GO term was integrin binding (FDR = 0.037). Integrins are transmembrane proteins that mediate cell adhesion, play an important role in promoting the invasiveness of glioma cells [48], and have been suggested as potential targets with diagnostic and prognostic value in glioma [49]. Several enriched GO terms were related to the activity of endopeptidases and collagen.…”
Section: Resultsmentioning
confidence: 99%
“…The failure of adhesion-block treatments may be due to the observed intra-and intertumoral heterogeneity, as typically preclinical tests use only one or two cell lines, which may not be representative of the distribution of integrin expression and adhesion in GBM tumors. Given that integrins play a crucial role in brain tumor infiltration 42 and GBM intratumor variability in integrin expressions 43 . New trials that aim to halt GBM recurrence by inhibiting radiation-induced invasion gains and signaling changes 11,44 , or kinase inhibitors 10 , could benefit from accounting for intra-and-intertumoral differences in single cell migration.…”
Section: Discussionmentioning
confidence: 99%
“…Several cancers, including glioblastoma, show modifications of the integrin pattern to be associated with tumour progression and poor patient survival, including a6b4, a6b1, avb6 and avb3 [119]. Several cancers, including glioblastoma, show modifications of the integrin pattern to be associated with tumour progression and poor patient survival, including a6b4, a6b1, avb6 and avb3 [119].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%
“…Integrins are key regulators of Src signalling, and are also deregulated in cancers, but are rarely mutated. Several cancers, including glioblastoma, show modifications of the integrin pattern to be associated with tumour progression and poor patient survival, including a6b4, a6b1, avb6 and avb3 [119]. An early sequencing study demonstrated a positive association between mutations in subunit a7 (encoded by ITGA7 gene), identified in 57% of prostate cancers, and increased cancer recurrence [120].…”
Section: The Src Signalling Axis Promotes Pancreatic Cancer Progressionmentioning
confidence: 99%